Earthquake Disaster Mitigation in the Building Industry - Noor Cholis Idham (Departement of Architecture, Universitas Islam Indonesia, 2020)
Architects have a significant role in the building industry, starting from the initial plan to detailed construction and even adaptive reuse of the building. However, the safety issues related to building under an earthquake is usually going to the effort of making its integrity; thus, it commonly became the matter of engineer works and the construction process. This paper studies how actually architect plays a more significant part to deal with earthquake disaster in the complete cycles of building. The architect roles in building safety are discussed in every step in the building industry. It is clear enough that the architects are the ones mastering in every precaution related to the mitigation, from macro to micro, from start to finish, and from one to other aspects of the building. Neglecting one of those will only leave the occupants in danger.Keywords: Architect role; Building safety; Earthquake disaster mitigation.